Effects of programmed teaching errors on acquisition and durability of self‐care skills. Issue 3 (24th April 2017) - Donnelly, Maeve G.; Karsten, Amanda M.
Abstract : This investigation sheds light on necessary and sufficient conditions to establish self‐care behavior chains among people with developmental disabilities. First, a descriptive assessment (DA) identified the types of teaching errors that occurred during self‐care instruction. Second, the relative effects of three teaching errors observed during the DA were evaluated across two behavior chains for three participants. Third, the effects of individual teaching errors were studied with a third behavior chain per participant. Teaching errors included prompting steps out of order, delivering the reinforcer at times other than immediately following correct completion of the training step, and failing to prompt completion of all steps within a teaching trial. All teaching errors included in the evaluation interfered with skill acquisition and disrupted performance of mastered skills. Results are discussed in terms of future research on the components of efficacious treatment packages for disseminating effective practices.